Analysis of Factors Affecting Student Interest in Studying in a Pandemic Period in Basic Social Sciences Elementary School Concepts - Sarah Azhari Pohan; Rahayu Condro Murti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Online learning is alternative learning that can be used so that teaching and learning activities can still be carried out during the COVID-19 pandemic. However, online learning activities have several obstacles that cause a decrease in interest in learning from some students. Interest in learning is the interest and willingness of one's soul to carry out activities happily to affect changes in knowledge, skills, and behavior. The problem related to this research is the decline in interest in learning for Elementary School Teacher Education students in online learning for the Basic Social Sciences Elementary Concepts course. This study aimed to analyze the factors that influence student interest in learning in the Basic Social Sciences Elementary School Concepts during online learning. This article uses descriptive qualitative data collection techniques, namely interviews and observations of 2nd-semester students of class 2D Primary School Teacher Education study program. The data analysis technique used the Milles and Huberman model with data reduction, data presentation, and conclusion drawing stages. The results showed that out of 10 students, 2 students' interest in learning was stable, while the other 8 students' interest in learning decreased. The factors that influence student learning interest are 1) Internet networks, 2) Media and Learning Resources, 3) Communication between Lecturers and Students, and 4) Environment. This study concludes that online learning affects student interest in learning, especially in the Basic Social Sciences Basic Concepts subject for Elementary School.